Do school Water, Sanitation, and Hygiene facilities affect students' health status, attendance, and educational achievements? A qualitative study in Nepal - Mohan Kumar Sharma; Ramesh Adhikari; Shanti Prasad Khanal; Devaraj Acharya; Edwin vanTeijlingen (Health Science Reports)
Abstract Background and Aims Access to safe and sufficient drinking Water, Sanitation, and good Hygiene (WASH) facilities in schools play a crucial role in preventing students from numerous Neglected Tropical Diseases, improving the learning environment in schools, and creating resilient communities living in a healthy environment. This study aims to explore the impact of combining WASH facilities on students' health status, school attendance, and educational achievements. Methods Four schools, two with improved and two without improved WASH facilities, were selected purposively from Dhanusha and Chitwan districts of Nepal. A total of 24 participants, 16 students, and eight teachers were also purposively selected based on the Theory of Data Saturation. The participants were interviewed face‐to‐face using study guidelines; Key Informants Interview for teachers and In‐depth Interview for students. The data were audio recorded and analyzed thematically using Dedoose 9.0.17 qualitative data management and analysis software. Results School WASH facilities have a significant impact on students' health and well‐being. Poor school‐WASH facilities hindered students' school attendance, particularly for menstruating girls. School without separate toilets for girls, including menstruation hygiene facilities, lack of water and soap, sanitary pad, and secure toilet's door often have higher rates of absenteeism among girls. Poor teacher and students' relationships, students' low interest in education, household chores, and participation in social customs also contribute to students' absence from school and low educational performance. It is important to note that inadequate WASH facilities affect not only students, but also teachers in the same school. Conclusion The lack of safe and sufficient drinking water, unimproved sanitation, and poor hygiene facilities were seen by students and teachers as reducing their health and well‐being, school attendance, and academic performance. Thus, schools need prioritize and promote the provision of improved WASH facilities for the betterment of students' health, attendance, and educational proficiency.